RETROSPECTIVE OBSERVATIONAL STUDY ON THE INCIDENCE OF ORAL COMPLICATIONS IN PATIENTS WITH DIABETES MELLITUS - Alberta Simona Tinu; Doina Lucia Ghergic; Mirel Stoian; Costin Coman; Raluca-Monica Comăneanu; Adi Lorean (Amaltea Medical Publishing House, 2018)
Objectives. We performed a retrospective observational analytical study to determine the incidence of complications in the oral cavity in a group of patients diagnosed with diabetes mellitus. Material and method. We have studied 68 diabetic patients, who have been referred to dental practices seeking specialized treatment. Patient data sheets were centralized, categorized, and statistically processed with IBM SPSS Statistics 22 and Microsoft Excel 2010 depending on: sex of patients, age, type of diabetes, time elapsed from diagnosis of diabetes, the environment of origin of the patients, the level of their training, the presence or absence of oral complications and the glycosylated hemoglobin value at presentation in the dental office. Results. The study group had an average age of 56.35 years, with being the best represented in the age group 44-54. The study group was composed predominantly of female, urban patients and higher-education patients. Half of the patients in the study group were diagnosed with diabetes more than 7 years ago, and the glycosylated hemoglobin value averaged 7.309. The incidence of complications of diabetes in the oral cavity of the studied group was, in decreasing order of frequency: periodontal disease, delayed healing of oral wounds, dental caries, salivary gland dysfunctions, alteration of taste sensations, burning sensation in the oral cavity, fungal infections and traumatic ulcers. Discussions. Both types of diabetes have long-term complications that are directly proportional to the duration and value of hyperglycemia. The most common oral complications of diabetes described in the literature have been found in the complications diagnosed n the study group patients. Conclusions. In the studied group, the number of complications in the oral cavity of a patient was statistically correlated with the glycosylated hemoglobin value and with the time elapsed since the diagnosis of diabetes mellitus. There was no statistically significant correlation between the number of complications found in the oral cavity and the level of patient training.